Crime fiction in German der Krimi - Hall, Katharina 1967- (European crime fictions, 2016)
"Crime Fiction in German: Der Krimi is the first volume in English to offer a comprehensive overview of German-language crime fiction from its origins in the early nineteenth century to its vibrant growth in the new millennium. As well as introducing readers to crime fiction from Germany, Austria, Switzerland and the former East Germany, the volume expands the notion of a German crime-writing tradition by investigating Nazi crime fiction, Jewish-German crime fiction,Turkish-German crime fiction and the Afrika-Krimi."--Page 4 of cover